2021
DOI: 10.1007/s40122-021-00312-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Conservative Treatment with Micronized Purified Flavonoid Fraction in Female Patients with Pelvic Congestion Syndrome

Abstract: Introduction: Pelvic congestion syndrome (PCS) may be effectively managed with conservative treatment in certain patients. Treatment with venoactive drugs is common, but supportive data are limited. This study evaluated the clinical efficacy of micronized purified flavonoid fraction (MPFF) in women with PCS. Methods: In a single-blind, placebo-controlled study, women with duplex ultrasound diagnosis of pelvic varicose veins (PVV) and PCS were randomized to MPFF 1000 mg once daily or placebo for 2 months. Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Additionally, 1000 mg of MPFF once daily has demonstrated benefits for treating PVI, significantly improving the clinical severity scores and quality of life and reducing thrombosis rates. 18 , 19 We observed favorable clinical outcomes with the implemented medical and surgical treatment.…”
Section: Discussionmentioning
confidence: 72%
“…Additionally, 1000 mg of MPFF once daily has demonstrated benefits for treating PVI, significantly improving the clinical severity scores and quality of life and reducing thrombosis rates. 18 , 19 We observed favorable clinical outcomes with the implemented medical and surgical treatment.…”
Section: Discussionmentioning
confidence: 72%
“…The commonly used drugs are spooning, e.g. , horse chestnut seed extract, the micronized purified flavonoid fraction (MPFF), and flavonoids[ 12 - 14 ]. Pentoxifylline is reported to target inflammatory cytokine release, leukocyte activation, and platelet aggregation at the microcirculatory level.…”
Section: Medical Therapymentioning
confidence: 99%
“…The pathophysiology of PCS pain includes an array of visceral, somatic and neurological pain generators [ 6 ]. In chronic lower extremity venous insufficiency, the pain state is related to abnormal vessel function [ 7 ]; about four decades ago, Kaupilla et al demonstrated a higher rate of histological vascular anomalies (such as fibrosis, muscular hypertrophy and widened ovarian diameter) in a group of PCS patients affected by CPP [ 8 ]. However, more recent views of pain states emphasize both peripheral and central contributors to nociception.…”
Section: Introductionmentioning
confidence: 99%